Reproductive ecology of tralhotos Anableps anableps and Anableps microlepis (Pisces: Osteichthyes: Cyprinodontiformes: Anablepidae) in the Paracauari river, island of Marajó, Pará, Brazil - Nascimento, Francylenna Lima do; Assunção, Maria Ivaneide da Silva (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2008)
This paper analyses and discusses population structure, reproduction, and aspects of the embryos of Anableps anableps and A. microlepis collected from the Paracauari River between 48º 30’ 20” W/ 00º 44’ 36” S and 48o 31’ 12” W/ 00º 43’ 34” S Marajó Island, state of Pará, Brazil, from August 2001 through April 2002. Sampling was carried out with trawls, shrimp nets, and casting-nets. A total of 1.203 specimens were collected and analyzed, from which 901 were A. anableps and 302 A. microlepis. Both species group themselves into schools of ten to 50 individuals; however, A. microlepis is predominant in the summer when the water is more saline, while A. anableps predominates in the winter when the water is fresh. Regarding sex ratio, it was of 1:1 for A. anableps, while A. microlepis females surpassed males in a ratio of 2:1. In relation to size, A. anableps (x = 240 mm) is on average smaller than A. microlepis (x = 270 mm), but females of each species were significantly larger than the males. Both species reproduce throughout the year, yet with reproductive peaks in distinct periods: A. anableps in winter and A. microlepis in summer. Each female produces ten to 31 oocytes that are released into the ovarian cavity when they reach 1.0-1.5 mm in diameter; when reaching 2.0 mm they attach themselves once again to the ovary’s wall, where they remain until eclosion. The embryos are released inside the ovarian cavity when development is complete and measure 45-47 mm in length at birth. Despite being mixed, each species maintains distinct strategies regarding structural and temporal organization time, and requiring different environmental conditions – possibly those that are more favorable for offspring development.